2021
DOI: 10.33719/yud.2021;16-3-887159
|View full text |Cite
|
Sign up to set email alerts
|

Incidental prostate cancer diagnosed after surgical treatment of benign prostatic hyperplasia

Abstract: Objective: Incidental prostate cancer (PCa) is defined as the clinically inapparent tumor detected after transurethral resection of prostate (TURP) or open prostatectomy with benign preoperative rectal examination, prostate specific antigen (PSA) and imaging. The aim of this study is to determine the incidence and clinical significance of incidental prostate cancer in our clinic. Material and Methods: A retrospective analysis was performed in patients who were treated with TURP or transvesical open prostatecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A 7-year study from the United States assessing the trends in diagnosis and management of IPC reported that patients diagnosed with T1a/b disease were significantly managed with active surveillance/watchful waiting and less likely to be treated with RP or radiation (Kord et al 2022 ). In a cohort of 1020 patients, IPC incidence was about 5.6%; 73.6% was managed with active surveillance, 3.5% underwent radical prostatectomy, 10.5% had radiotherapy, and 12.2% had androgen blockade (İlktaç et al 2021 ). More than 90% of IPC cases at diagnosis are International Society of Urological Pathology (ISUP) grade group 1, and active surveillance (AS) is now the standard of care and safe management strategy for most patients (Capitanio et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 7-year study from the United States assessing the trends in diagnosis and management of IPC reported that patients diagnosed with T1a/b disease were significantly managed with active surveillance/watchful waiting and less likely to be treated with RP or radiation (Kord et al 2022 ). In a cohort of 1020 patients, IPC incidence was about 5.6%; 73.6% was managed with active surveillance, 3.5% underwent radical prostatectomy, 10.5% had radiotherapy, and 12.2% had androgen blockade (İlktaç et al 2021 ). More than 90% of IPC cases at diagnosis are International Society of Urological Pathology (ISUP) grade group 1, and active surveillance (AS) is now the standard of care and safe management strategy for most patients (Capitanio et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%